Increasing productivity and management of IRT business "kalian kripik" In Kelurahan Karang Berombak, Kecamatan Medan Barat, Kota Medan - Emalisa; Iskandarini; Fauzia, Lily; Negara Lubis , Satia; Bahauddin Barus, Mozart (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
After the idea, production machinery and equipment is the capital that a production business must have in order to run. The more complete and modern the tools and machines that a business has, the more business productivity will increase, which in turn can increase business revenues. This service aims to increase the productivity and management of IRT 'Kalian Kripik' which produces onion cakes from various original flavors from agricultural products such as potatoes, sweet potatoes and sweet potatoes. Devotion is done by providing science and technology assistance in the form of Ampia machines and Digital Scales, as well as business management training in the form of training in calculating depreciation costs, bookkeeping, and business analysis. After this service, IRT ‘Kalian Kripik’ has been able to improve the quality and quality of its products. The results of dedication show that with the help of machines and tools that are given by the Partner, they can improve the quality of their products, weigh the ingredients and production more accurately, be able to manage business better in the form of bookkeeping activities, calculation of depreciation and business analysis.